Teamwork on employee performance: a case study of Royal Malaysian Customs, Kuching, Sarawak / Nor Dalila Murtadza & Khatijah Mostapha - Murtadza, Nor Dalila; Mostapha, Khatijah (2013)
This research analyzes the teamwork on employee performance in Royal Malaysian Customs, Kuching, Sarawak. Cohen & Bailey (1999) stated that an organization which emphasize more on teams have resulted in increased employee performance, greater productivity and better problem solving at work. The main purpose of this study is to identify the main factors in teamwork which are team trust, esprit de corps, recognition and reward that contribute to the employee performance. The researchers examine the relationship between the variables which are team trust, esprit de corps, recognition and reward on employee performance. The influence of gender on the employees’ work performance was also being analyzed in this study. In addition, the researchers have provided recommendations on improving the teamwork. There were 165 respondents participated in this survey. Based on the findings, it shows that team trust become the main factor in enhancing teamwork and these variables which are esprit de corps, team trust and reward and recognition have a significant and positive relationship with the employee performance. The study also reveals that gender has no influence on their work performance. In order to improve the teamwork effectiveness, the organization could emphasize on the group cohesion, encourage an active participation from the team members as well as increase an effective communication and interactions among the employees in Royal Malaysian Customs, Kuching, Sarawak.